Qajar role in reconstruction operations in the holy scenes scene Kazimi a model - مري حسن البنداوي أحمد; عبد الهادي الزيرجاوي قاسم (Al-Adab Journal, 2018)
The scene Kazimi cleanser important shrines as it represents the shrine of religious significance, as it was the religious factor significant impact on the evolution of the holy city of Kadhimiya and Ncaiha, because there shrine (peace be upon them), is that the nucleus of housing in the city, then expanded until it became a center, which make it a tourist and commercial city of religious virtue of these factors. From this point of Azad researchers wish to address their search marked (Qajar role in reconstruction operations in the holy scenes scene Kazimi a model). The study of an introduction and two chapters and a conclusion has been dealt with. It handled the first chapter of the Holy Kazimi scene since the Safavid occupation of Baghdad in 1508 and even took control of the Qajar Persia at the end of the eighteenth century. The most important characteristic of the first quarter during the Safavid period and Covenant ulnar even took control of the Qajar on the reins of power in Persia is to build a kindergarten Kadhimiya holy and adorned with colored Eachan and work Iron Cage by Shah Abbas Safavid and visited the holy scene with a large delegation of clerics and ministers, as well as compensation scene Holy lampstands four instead of two minarets and the mosque building Safavid and adorn the shrine from the inside through the use of wood and ebony jujube and others. Add to the sultans of the Safavids and the Ottomans Sharif visited the shrine when their occupation to the city of Baghdad in general, Kadhimiya in particular. Chapter II took the sacred scene upon receipt Qajari judgment, especially when the sultans Alqajayan adding increasing reconstruction on the sacred scene by doing Ptzhab Alqptin Ahariftin and heads Lighthouses gold to witness the shrine holy aesthetic in construction, as well as the reconstruction of the scene blessed and Ngtit walls to cut off small mirrors to complete the adornments and engraving soles Alqptin beautiful inscriptions have been the focus in this chapter on the reconstruction operations Tgert through Qajari judgment, especially as these operations experiencing aspect of apathy because of the relations between the Qajar and the state of the Ottoman Empire which affects the reconstruction operations as well as up on the situation Persian community that was present in the scene blessed. It was referring to travelers who have visited the city and then gave the impression the sacred landscape as well as the Qajari Sultan Nasser al-Din Shah to visit the holy scene and documented travelers and this impression from the scene blessed. Finally at the conclusion of the study was to give some Alastnajat that enable researchers that supplied.